2013
DOI: 10.1021/nl401439b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Lithium–Oxygen Battery Behavior

Abstract: In this Letter we report an electrochemical and morphological study of the response of lithium-oxygen cells cycled at various temperatures, that is, ranging from -10 to 70 °C. The results show that the electrochemical process of the cells is thermally influenced in an opposite way, that is, by a rate decrease, due to a reduced diffusion of the lithium ions from the electrolyte to the electrode interface, at low temperature and a rate enhancement, due to the decreased electrolyte viscosity and consequent increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 26 publications
8
55
1
Order By: Relevance
“…[120][121][122] A drawback, still associated with the cathode and so far unsolved, is the low power capability of the cell, which is closely correlated to the low current densities attainable, typically on the order of 0.1 mA cm −2 . [ 75,94,123 ] Alternative, nanostructured carbon confi gurations, such as graphene, tubes, foams, and nanofi bers might bring a solution to this, since their large surface and high electronic conductivity are expected to enhance the kinetics of the electrochemical process, by providing an effective Li + fl ux and lower values of charge transfer resistance. [ 76,124 ] On the other hand, this approach may contribute to carbon .…”
Section: The Cathode Substratementioning
confidence: 99%
“…[120][121][122] A drawback, still associated with the cathode and so far unsolved, is the low power capability of the cell, which is closely correlated to the low current densities attainable, typically on the order of 0.1 mA cm −2 . [ 75,94,123 ] Alternative, nanostructured carbon confi gurations, such as graphene, tubes, foams, and nanofi bers might bring a solution to this, since their large surface and high electronic conductivity are expected to enhance the kinetics of the electrochemical process, by providing an effective Li + fl ux and lower values of charge transfer resistance. [ 76,124 ] On the other hand, this approach may contribute to carbon .…”
Section: The Cathode Substratementioning
confidence: 99%
“…This response has been shown to vary depending on an increasingly substantial list of parameters including: the O 2 pressure and purity in the system, 14,40,41 operating temperature, [42][43][44] …”
Section: 29mentioning
confidence: 99%
“…,48 Previous studies 49 also23 have reported that high temperature might favor charge transport through Li 2 O 2 , especially at low current densities, and yield high discharge capacity. Although this mechanism is not addressed in the present work, it can be incorporated into our mesoscale model in the future by coupling the appropriate governing equations for charge transport through Li 2 O 2 .Figure 13.…”
mentioning
confidence: 97%
“…47 However, an increase in temperature can significantly increase O 2 diffusivity in electrolytes. For example, it has been reported that the O 2 diffusivity in TEGDME solvent follows the relationship to temperature as: 48 Here, ‫ܦ‬ ଶଽ଼ is the O 2 diffusivity at 298 K, and ‫ܦ‬ ் is the O 2 diffusivity at temperature ܶ. Figure 13 shows the calculated discharge curves for TEGDME solvent at four different temperatures: 283, 298, 323, and 343 K, respectively.…”
mentioning
confidence: 99%